Optimization of Titanium Surface for Live Cells - Puchnin, Maxim; Pešlová, Františka; Kuchař, Jiří (Manufacturing Technology Journal, 2025)
The present paper is focused on the study of the characteristics of selected titanium alloys before and after heat treatment. The specimens were cooled both in water and liquid nitrogen from 900°C and 1000°C for pure titanium and from 1000°C and 1100°C for the Ti-6Al-4V alloy. Further, the paper deals with line MG63 live bone cells deposited on a titanium base substrate. Proliferation and differentiation are monitored of cells during 7-day in vitro cultivation portraying growth of cells on a biologically selected material.
Keywords: Titanium alloys; Live cells; Mechanical properties; Scanning electron microscopy; Heat treatment